Morphogenesis of grape microplants in in vitro culture using biologically active substances of synthetic origin - Krasinskaya, Tatiana A.; Zmushko, Alexandr A. (Experimental Biology and Biotechnology, 2019)
The aim of research was to study the influence of biologically active substances of synthetic origin (6-benzylaminopurine, thidiazuron and kinetin) on morphological development of microplants of cv. Agat donskoy and Mars on proliferation stage. Cv. Mars has the largest potential for gemmogenesis. On media with kinetin cv. Mars formed roots. On media with thidiazuron cv.Agat donskoy formed callus at base of conglomerate. Thidiazuron and kinetin on 4th subculture cause increase of percent of vitrified plants to 52.8–59.8 % depending on cultivar. During 4th and 5th subcultures modified MS culture with 1.1 and 1.5 mg /l BAP resulted in large number of normal developed microplants during gemmogenesis, without negative effects detected when using thidiazuron and kinetin. On average, for studied cultivars, use of modified MS culture with 1.1 and 1.5 mg /l BAP promoted activation of gemmogenesis, propagation coefficient was 4.3 and 4.7.